Orexin/Hypocretin and MCH Neurons: Cognitive and Motor Roles Beyond Arousal - Concetti, Cristina; Burdakov, Denis (Frontiers in Neuroscience, 2021)
The lateral hypothalamus (LH) is classically implicated in sleep-wake control. It is the main source of orexin/hypocretin and melanin-concentrating hormone (MCH) neuropeptides in the brain, which have been both implicated in arousal state switching. These neuropeptides are produced by non-overlapping LH neurons, which both project widely throughout the brain, where release of orexin and MCH activates specific postsynaptic G-protein-coupled receptors. Optogenetic manipulations of orexin and MCH neurons during sleep indicate that they promote awakening and REM sleep, respectively. However, recordings from orexin and MCH neurons in awake, moving animals suggest that they also act outside sleep/wake switching. Here, we review recent studies showing that both orexin and MCH neurons can rapidly (sub-second-timescale) change their firing when awake animals experience external stimuli, or during self-paced exploration of objects and places. However, the sensory-behavioral correlates of orexin and MCH neural activation can be quite different. Orexin neurons are generally more dynamic, with about 2/3rds of them activated before and during self-initiated running, and most activated by sensory stimulation across sensory modalities. MCH neurons are activated in a more select manner, for example upon self-paced investigation of novel objects and by certain other novel stimuli. We discuss optogenetic and chemogenetic manipulations of orexin and MCH neurons, which combined with pharmacological blockade of orexin and MCH receptors, imply that these rapid LH dynamics shape fundamental cognitive and motor processes due to orexin and MCH neuropeptide actions in the awake brain. Finally, we contemplate whether the awake control of psychomotor brain functions by orexin and MCH are distinct from their “arousal” effects.